PENGARUH PENGAPLIKASIAN SAK-ETAP DAN KOMPETENSI PEGAWAI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI KASUS PADA PT XYZ) - Dede Puspa Pujia; Hurian Kamela; Zenzibar; Virza Hadrianti; Aziz Septiatin; Adibah Yahya (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2022)
In this study the author tried to look at 2 variable that affect the quality of financial statements. The first variable is the application of SAK-ETAP and the second variable is the competence of accounting employees The object of this study is the accounting employees of PT XYZ who are also a sample. Multiple linear regression is used to analyze research results and the processing of research data with SPSS 22. Partially, the results of this study are the application of SAK-ETAP had no effect on the quality of financial statements, while the competence of accounting employees had an effect on the quality of financial statements.